Early warning systems in Indonesian Islamic banks: A comparison of Islamic commercial and rural banks - Imron Mawardi; Muhammad Ubaidillah Al Mustofa; Tika Widiastuti; Wahyu Wibisono Wahid (Cogent Economics & Finance, 2023)
The study examines the stability of Indonesian Islamic Commercial Bank (ICB) and Islamic Rural Bank (IRB) by employing a Markov Switching Dynamic model of two regimes, stable (tranquil) and unstable (crisis). This study utilizes monthly data between December 2007 and April 2022. Findings show that both ICB and IRB have greater probabilities of remaining in the tranquil regime compared to the period of crisis. Even though ICB Z-scores have a wider range of volatility than IRB Z-scores, the ICB has been shown to recover from crises faster than the IRB. The differences in characteristics between ICB and IRB, as well as swings in the Z-score, do not provide resilience benefits. Thus, both ICB and IRB are equally vulnerable to the crisis. This study's findings could be used to generate policy for the relevant stakeholders of Islamic banking industries.
Keywords: G21; 330; bank vulnerability; early warning system; Islamic banking; Markov Switching; Z-score